2009
DOI: 10.1007/s00384-009-0660-z
|View full text |Cite
|
Sign up to set email alerts
|

The morbidity surrounding reversal of defunctioning ileostomies: a systematic review of 48 studies including 6,107 cases

Abstract: The consequences of anastomotic leakage following colorectal resection are severe. However, the consequences of stoma reversal are often underestimated. Surgeons should adopt a selective strategy regarding the use of defunctioning ileostomy, and counsel patients further prior to the original surgery. In this way, patients at low risk may be spared the morbidity of stoma reversal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
305
3
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(346 citation statements)
references
References 77 publications
22
305
3
16
Order By: Relevance
“…It has been speculated that stoma closure can be another risk factor for PMC, which associates all the previous to an excluded and defunctioned bowel with altered flora, that could be more susceptible to C.diff ity [8] . In a recent systematic review [7] , the high morbidity associated to ileostomy reversal raised concerns over the real indication of diverting stomas related to clinical outcomes, and if a better selection of patients should be made. Luglio et al [9] , consider that if there is a > 5% risk of anastomotic leak in the primary operation, a protective stoma must be created.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been speculated that stoma closure can be another risk factor for PMC, which associates all the previous to an excluded and defunctioned bowel with altered flora, that could be more susceptible to C.diff ity [8] . In a recent systematic review [7] , the high morbidity associated to ileostomy reversal raised concerns over the real indication of diverting stomas related to clinical outcomes, and if a better selection of patients should be made. Luglio et al [9] , consider that if there is a > 5% risk of anastomotic leak in the primary operation, a protective stoma must be created.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical infection of the wound is always a relevant one. A recent systematic review on ileostomy reversal reported an overall mortality of 0.4% [7] , with values ranging from 0% to 4% in different studies. The aim of our study was to review our institutional series of ileostomy reversals and identify possible risk factors for postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…However, diverting loop‐ileostomy potentially increases the risks for stoma‐related complications including small bowel obstruction (SBO), stoma prolapse, stoma retraction, parastomal hernia, parastomal dermatitis, and mucocutaneous dehiscence. Risks for stoma‐related complications are reportedly 5‐46% 6, 7, 8, 9…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis in 2009 concluded that stoma closure results in additional morbidity for 17% of patients, a 3.7% reoperation rate and 0.4% mortality rate. 22 Furthermore, prior to reversal, stomas have been associated with complications like dermatitis, parastomal hernia, stenosis, hemorrhage, prolapse, retraction and dehydration in up to 60% of patients, 12,[23][24][25] and the incidence increases with the duration of the stoma. 12 Therefore, we sought to further characterize factors associated with non-reversal and delayed reversal among elderly patients, those most at risk for non-reversal, to aid in pre-operative counseling and realistic expectation setting.…”
Section: Discussionmentioning
confidence: 99%